Drug Development: A Helical Polypeptide‐Based Potassium Ionophore Induces Endoplasmic Reticulum Stress‐Mediated Apoptosis by Perturbing Ion Homeostasis (Adv. Sci. 14/2019). Issue 14 (17th July 2019) - Lee, DaeYong; Lee, Soo‐Hwan; Noh, Ilkoo; Oh, Eonju; Ryu, Hyunil; Ha, JongHoon; Jeong, SeongDong; Yoo, Jisang; Jeon, Tae‐Joon; Yun, Chae‐Ok; Kim, Yeu‐Chun
Abstract : In article number of1801995, Chae‐Ok Yun, Yeu‐Chun Kim, and co‐workers develop helical polypeptide‐based potassium ionophores that can drive out potassium ions from the cytosol. The perturbed potassium homeostasis strongly inflicts endoplasmic reticulum stress to cells and then creates severe oxidative environments, thereby triggering apoptosis. The novel potassium ionophore will be used as a new anticancer agent.